2020
DOI: 10.20944/preprints202002.0364.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HSP70/IL-2 Treated NK Cells Effectively Cross the Blood Brain Barrier and Target Tumor Cells in a Rat Model of Induced Glioblastoma Multiforme (GBM)

Abstract: Natural killer (NK) cell therapy is one of the most promising treatments for Glioblastoma Multiforme (GBM). However, this emerging technology is limited by the availability of sufficient numbers of fully functional cells. Here, we investigated the efficacy of NK cells that were expanded and treated by interleukin-2 (IL-2) and heat shock protein70 (HSP70), both in vitro and in vivo. Proliferation and cytotoxicity assays were used to assess the functionality of NK cells in vitro, after which treated and naï ve N… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The TKD peptide, a 14-amino acid sequence from the Heat shock protein 70 (HSP70), has been demonstrated to stimulate the cytolytic, proliferative and migratory ability of NK cells against target cells, expressing the membrane form of HSP70 on their surface, through the engagement of CD94 [ 93 , 94 ]. TKD-expanded and activated NK cells by the Royan Institute and Tehran University of Medical Sciences are tested against patient-derived glioblastoma cells with membrane-bound HSP70 (Additional file 1 : Table S1, row 16) [ 95 ]. Moreover, priming agents, such as the IL-15 superagonist ALT-803 and the IL-2 recombinant fusion protein ALT-801 from Altor Bioscience, have been tested in combination with NK cells in a few clinical studies (Additional file 3 : Table S3, rows 3 [ 96 ] and 6 [ 97 ]).…”
Section: Clinical Manufacturing Of Nk Cell Therapiesmentioning
confidence: 99%
“…The TKD peptide, a 14-amino acid sequence from the Heat shock protein 70 (HSP70), has been demonstrated to stimulate the cytolytic, proliferative and migratory ability of NK cells against target cells, expressing the membrane form of HSP70 on their surface, through the engagement of CD94 [ 93 , 94 ]. TKD-expanded and activated NK cells by the Royan Institute and Tehran University of Medical Sciences are tested against patient-derived glioblastoma cells with membrane-bound HSP70 (Additional file 1 : Table S1, row 16) [ 95 ]. Moreover, priming agents, such as the IL-15 superagonist ALT-803 and the IL-2 recombinant fusion protein ALT-801 from Altor Bioscience, have been tested in combination with NK cells in a few clinical studies (Additional file 3 : Table S3, rows 3 [ 96 ] and 6 [ 97 ]).…”
Section: Clinical Manufacturing Of Nk Cell Therapiesmentioning
confidence: 99%
“…The declined cytotoxic function of Hsp70-treated NK cells against K562 and SKOV3 cells in the present study (Fig. 5 ; Additional file 3 : Figure S3) can be explained by the dual function of Hsp70 which can also promote the cancer cells viability [ 27 , 43 47 ]. Furthermore, considering the qRT-PCR results, it can be claimed that treating with Hsp70 led to a reduction in the NK cell lysis capacity compared to the other group.…”
Section: Discussionmentioning
confidence: 80%
“…Functionality can be induced using exogenous molecules regulating the NK cells effector factors such as IL-2, IL-15 and IL-21. They do so by increasing the expression of co-inhibitory receptors (PD-1), inhibitory receptors (NKG2A) and the upregulation of the activating receptors like NKG2D.All these changes can impair the balance of activating/inhibitory signals and consequently result in the exhaustion of NK cell functions [ 20 , 21 , 27 , 39 – 41 ]. Other factors that can suppress NK cells function during differentiation and activation are suppressive cytokines such as TGF-β which induces the downregulation of activating receptors [ 12 , 13 , 20 , 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant teams analyzed the glioma data obtained from TCGA and verified the expression of differential proteins in the tissues or body fluids of glioma patients, animal models and cell lines. Common targets are GFAP (Wang et al, 2018), HSP70 (Sharifzad et al, 2020), VEGF (Nicolas et al, 2019), BDNF (Huo & Chen, 2019, ECM (Tejero et al, 2019), FN1 (Yu et al, 2020;Gu, Gu & Shou, 2014;Guo, Heller & Thorslund, 2016;Liao et al, 2018), CD44 (Mooney et al, 2016), Fransgelin-2, Short Hairpin RNAGLN and GRN (Ness, Riemenschneider & Baches., 2009;Trigos et al, 2019) etc. Previous research suggested that TAGLN2 might be involved in progression due to its higher expression in glioblastomas compared to IDH1/2 WT gliomas of lower grades (Beyer et al, 2018;Han et al, 2017).…”
Section: Discussionmentioning
confidence: 99%